Association of Betatrophin, TNF-α and IL-6 with diabetic microvascular and macrovascular complications - Gozel, Nevzat; Melek Burkay Yakar, Elif; Onalan, Erhan; Ferit Gursu, Mehmet (Annals of Medical Research, 2021)
Aim: The most important goal in the treatment of Diabetes Mellitus is to protect patients from micro and macro complications. Inflammatory cytokines and betatrophin have been reported to play a role in diabetic micro and macro complications. This study aimed to investigate the effect of serum Betatrophin, TNF-α and IL-6 levels on diabetic micro and macro complications in patients with type 2 Diabetes Mellitus.
Keywords: Betatrophin; diabetes mellitus; IL-6; TNF-α; Type 2/complications